AMPH-IMA04: A REVISED HYPERCARD PROGRAM TO DETERMINE THE NAME OF AN AMPHIBOLE FROM CHEMICAL ANALYSES ACCORDING TO THE 2004 INTERNATIONAL MINERALOGICAL ASSOCIATION SCHEME - Mogessie A.; Ettinger K.; Leake B.E. (My University, 2004)
In 2004, the International Mineralogical Association (IMA) amended the IMA 97 amphibole classification and nomenclature scheme byadding a fifth group to include the recently discovered B(LiNa) amphiboles ferriwhittakeriite and ferri-ottoliniite, which cannot be fitted into the four major amphibole groups. New root-names such as sodic-pedrizite in the Mg-Fe-Mn-Li group and obertiite and dellaventuraite in the sodic group along with two new prefixes, parvo and magno have also been added. As result it has become necessaryto modifythe AMPH-IMA97 amphibole-naming program. The new program (AMPH-IMA04) allows single input or automatic input of as manyamphibole analyses as are available following a set input format. Any of three different calculation schemes for dealing with an amphibole analysis can be chosen: (1) complete chemical analyses can be calculated to 24(O, OH, F, Cl); (2) analyses with determined FeO and Fe2O3, MnO and Mn2 O3 but without H2O can be calculated to 23(O); and (3) electron microprobe analyses with only total Fe determined and without H2O can be calculated to 23(O) with IMA97-recommended normalization for Fe3+ and Fe2+ values. In addition a stoichiometric calculation of Mn2+ and Mn3+ is considered and implemented for the Mn-bearing sodic amphiboles in order to take care of electron microprobe analyses of such amphiboles where the total Mn is given as Mn2+.
Keywords: amphibole